Estrategias didácticas innovadoras y su impacto en los problemas del aprendizaje de la lectoescritura de los estudiantes de básica media de la escuela “República De España”, cantón Buena Fe, periodo lectivo 2023-2024. - Lara Paredes, Mayra Katherine (2024)
The development project was carried out with the objective of analyzing innovative teaching strategies and their impact on the problems of learning to read and write among middle school students at the “República de España” school, in the Buena Fe canton, provinces of Los Ríos, school period. 2023-2024. This research will be framed in a qualitative-quantitative approach, through descriptive, exploratory, bibliographic and field research, through direct observation and application of surveys through a structured questionnaire on the Google Forms platform with selection questions. For the students and interviews via Microsoft Teams for the director and the teachers under study. This study allowed, based on the diagnosis of the current situation regarding teaching strategies, to design a training plan aimed at teachers of the “República de España” School of Basic Education on innovative teaching strategies and their impact on the problems of the learning. of the reading and writing of basic secondary school students, and skills to promote autonomous learning in the formation of transformative subjects. The results obtained allow us to demonstrate the importance of innovative teaching strategies that can be applied in the teaching-learning process, strengthening the content based on innovative strategies for the development of literacy activities, an instrument that will be of great support for the training of students. teaching students.